Theoretical Studies of Substitutionally Doped Single-Walled Nanotubes - Charles See Yeung; Ya Kun Chen; Yan Alexander Wang (Journal of Nanotechnology)
The rich chemistry of single-walled carbon nanotubes (SWCNTs) is enhanced by substitutional doping, a process in which a single atom of the nanotube sidewall is replaced by a heteroatom. These so-called heteroatom-substituted SWCNTs (HSWCNTs) exhibit unique chemical and physical properties not observed in their corresponding undoped congeners. Herein, we present theoretical studies of both main group element and transition metal-doped HSWCNTs. Within density functional theory (DFT), we discuss mechanistic details of their proposed synthesis from vacancy-defected SWCNTs and describe their geometric and electronic properties. Additionally, we propose applications for these nanomaterials in nanosensing, nanoelectronics, and nanocatalysis.